SmeOP-TolC(Sm) Efflux Pump Contributes to the Multidrug Resistance of Stenotrophomonas maltophilia - Lin, Cheng-Wen (American Society for Microbiology, 2014)
A five-gene cluster, tolC(Sm)-pcm-smeRo-smeO-smeP, of Stenotrophomonas maltophilia was characterized. The presence of smeOP and smeRo-pcm-tolC(Sm) operons was verified by reverse transcription (RT)-PCR. Both operons were negatively regulated by the TetR-type transcriptional regulator SmeRo, as demonstrated by quantitative RT-PCR and a promoter-fusion assay. SmeO and SmeP were associated with TolC(Sm) (the TolC protein of S. maltophilia) for the assembly of a resistance-nodulation-cell-division (RND)-type pump. The compounds extruded by SmeOP-TolC(Sm) mainly included nalidixic acid, doxycycline, amikacin, gentamicin, erythromycin, leucomycin, carbonyl cyanide 3-chlorophenylhydrazone, crystal violet, sodium dodecyl sulfate, and tetrachlorosalicylanilide.